J Child Dev Disord 2019
DOI: 10.36648/2472-1786.5.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Socio Demographic Profile of Children with Autism Spectrum Disorders from a Tertiary Care Hospital in Kashmir, India

Abstract: Background: In spite of advances in assessment and management of patients with Autism Spectrum Disorders (ASDs) in west, developing countries including India are lagging far behind in child psychiatry, let alone ASDs. The aims of our study were to find the socio-demographic and clinical profile of children with ASDs in a child psychiatry unit. Methods and Materials: This was a Cross sectional observational descriptive study conducted in Outpatient child psychiatry clinic. Semi-structured questionnaire was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
1
1
Order By: Relevance
“…This mean age of diagnosis is slightly higher than the 35.8 months that was found in the previous study in Sri Lanka [ 6 ]. The mean age of diagnosis, as revealed by this study is much lower when compared to the findings from studies in the other parts of South and Southeast Asia, where the mean age of presentation was much higher at 5.5 years [ 10 ], 6.5 years [ 13 ], and 6.6 years [ 8 ]. However, it is higher when compared to a study carried out in Egypt and Saudi Arabia [ 11 ], in which the mean age of presentation was 1.7 years in Saudi Arabia and 2.25 years in Egypt.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This mean age of diagnosis is slightly higher than the 35.8 months that was found in the previous study in Sri Lanka [ 6 ]. The mean age of diagnosis, as revealed by this study is much lower when compared to the findings from studies in the other parts of South and Southeast Asia, where the mean age of presentation was much higher at 5.5 years [ 10 ], 6.5 years [ 13 ], and 6.6 years [ 8 ]. However, it is higher when compared to a study carried out in Egypt and Saudi Arabia [ 11 ], in which the mean age of presentation was 1.7 years in Saudi Arabia and 2.25 years in Egypt.…”
Section: Discussioncontrasting
confidence: 87%
“…This is contrary to previous studies conducted in Sri Lanka, which stated that epilepsy is among the most common co-morbidities in autistic children, with it being prevalent in 10.6% according to one study [ 6 ], and 19.8% according to another [ 18 ]. A study conducted in India [ 13 ] revealed that ADHD and epilepsy were the commonest co-morbidities. A Malaysian study [ 10 ] also concluded thus, stating that ADHD was found in 14.2% of the children and epilepsy in 9.4%.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one of the main findings was that of the 67 children and adolescents with ASD accessing psychiatric care, most were males (60 males; 89.6%), this being consistent with the literature. 26 , 27 , 28 , 29 , 30 , 31 The literature has reported that male children with ASD display more externalising behaviours than their female counterparts such as aggression and hyperactivity, 32 which may explain an earlier presentation to psychiatric services. Other possibilities for the male predominance may include sex-linked genetic and hormonal factors that are thought to contribute to the risk of developing ASD, for example, prenatal hormones could diminish risk in female children while promoting it in males.…”
Section: Discussionmentioning
confidence: 99%